Comparative study of structural, acidic and hydrophilic properties of Sn-BEA with Ti-BEA using periodic density functional theory - Shetty, Sharan; Kulkarni, Bhakti S.; Kanhere, Dilip G.; Goursot, Annick; Pal, Sourav (Journal of Physical Chemistry B, 2008)
Periodic density functional theory has been employed to characterize the differences in the structural, Lewis acidic and hydrophilic properties of Sn-BEA and Ti-BEA. We show that the incorporation of Sri increases the Lewis acidity of BEA compared to the incorporation of Ti. Hence, the present work gives insight into the role of Sn in increasing the efficiency of the oxidation reactions. The results also justify that the percentage of Sri substituted in BEA is less than Ti. The structural analysis shows that the first coordination shell of Sri is larger than that of Ti. However, the second coordination of both sites remains the same. The water adsorption properties of these substituted zeolites are quantified. Moreover, we explain the higher Lewis acidity of Sn than the Ti site on the basis of the Fukui functions and charge population analysis.